Lysine-based amino-functionalized lipids for gene transfection: the protonation state in monolayers at the air–liquid interface. Issue 30 (20th July 2017) - Tassler, Stephanie; Wölk, Christian; Janich, Christopher; Dobner, Bodo; Brezesinski, Gerald
Abstract : The TRXF results indicate a linear dependence of the protonation state on the required area per molecule of the lysine-based amino-functionalized lipids. Abstract : Cationic lipids are considered as non-viral carriers for genetic material used in gene therapy. They have no carcinogenic potential and cause low immune response compared to existing viral systems. The protonation degree of these cationic lipids is a crucial parameter for the binding behavior of polynucleotides ( e.g., DNA). Newly synthesized peptide-mimic lysine-based amino-functionalized lipids have been investigated in 2D models as monolayers at the air–liquid interface. Standard surface pressure – area isotherms have been measured to prove the layer stability. Total reflection X-ray fluorescence (TRXF) has been used as a surface sensitive analytical method to estimate the amount of counterions at the head groups. Using a standard sample as a reference, the protonation degree of these cationic lipids can be quantified on buffers with different pH values. It is found that the protonation degree depends linearly on the packing density of the lipid monolayer.